PERBEDAAN JUMLAH KROMOSOM IKAN TOMAN (Channa micropeltes) DENGAN IKAN SERANDANG (Channa pleuropthalmus) - Resfiza .; Muslim ,; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2014)
ABSTRACT The aims of this research was to comparing the chromosomes number from Channidae family. They are giant snakehead (C. micropeltes) and ocellated snakehead (C. pleuropthalmus). The research was conducted in December 2013-January 2014 in the aquaculture Laboratory, Aquaculture Study Program, Agriculture Faculty, Sriwijaya University for acclimatization of fish, Animals Fisiology Laboratory, Biology Sriwijaya University for made preparations and Laboratory Â genetic and fish reproductcy Departement of aquaculture, Maritime Affairs and Fishery Faculty Bogor Agriculture Institute for chromosome analysis. Weight of the fish used in this study was 500-600 gram. Analysis performed on chromosome preparations of both fish used squash method with modifications and stain with Giemsa. Based on the results of the two types of fish that Channa genus that have different numbers of chromosomes where giant snakehead has 50 of chromosome number with range 2n=40-50 and ocellated snakehead has 46 of chromosome number with range 2n=43-46. Â  Keywords : Channa micropeltes, Channa pleuropthalmus, chromosomes